2014
DOI: 10.1016/j.jpain.2013.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Voluntary Wheel Running in Rats Is Dependent on the Site of Inflammation: Evidence for Voluntary Running as a Measure of Hind Paw-Evoked Pain

Abstract: Decreased voluntary wheel running has recently been proposed as a preclinical pain measure for inflammatory pain, but whether this reflects pain evoked by use of the affected limbs is unknown. To assess the role of inflammation site as a determinant of this measure, complete Freund’s adjuvant (CFA), formalin, or equivolume vehicle was subcutaneously injected into the plantar surface of the hindpaws (bilateral) or L1 dorsum dermatome (leaving paws unaffected) of male Sprague Dawley rats. CFA-induced hindpaw mec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
46
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(56 citation statements)
references
References 36 publications
9
46
0
1
Order By: Relevance
“…Results from our pain-evoked experiments are consistent with previous studies showing that depression of wheel running recovers faster than reversal of evoked hypersensitivity (Cobos et al, 2012; Grace et al, 2014). This difference between pain-depressed and pain-evoked measures of nociception highlights one of the advantages of wheel running as a measure of nociception, namely that it reveals whether allodynia and hyperalgesia produce a functional deficit in behavior.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Results from our pain-evoked experiments are consistent with previous studies showing that depression of wheel running recovers faster than reversal of evoked hypersensitivity (Cobos et al, 2012; Grace et al, 2014). This difference between pain-depressed and pain-evoked measures of nociception highlights one of the advantages of wheel running as a measure of nociception, namely that it reveals whether allodynia and hyperalgesia produce a functional deficit in behavior.…”
Section: Discussionsupporting
confidence: 91%
“…8), such that wheel running is almost completely inhibited in the first day after CFA administration and slowly recovers over the next 14 days. Previous studies in which access to the running wheel was limited needed bilateral injections of CFA into the hindpaws to produce a reduction in wheel running (Cobos et al, 2012; Grace et al, 2014). The sensitivity of our test is probably related to continuous access to the wheel in the rat’s home cage as opposed to assessing wheel running for 1 hr a day.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…lactic acid and i.pl. CFA is consistent with previous studies that reported depression by these noxious stimuli of other behaviors, including liquid food consumption, locomotor activity, and wheel running in mice [8; 9; 27; 43] and burrowing, wheel running, and operant responding for electrical brain stimulation in rats [1; 15; 21; 22]. Nesting may be advantageous relative to these other behaviors as a dependent measure for studies of pain-depressed behavior for several reasons.…”
Section: Discussionsupporting
confidence: 89%